Pulmonary and systemic toxicity in rats following inhalation exposure of 3-D printer emissions from acrylonitrile butadiene styrene (ABS) filament. (14th October 2020) - Farcas, Mariana T.; McKinney, Walter; Qi, Chaolong; Mandler, Kyle W.; Battelli, Lori; Friend, Sherri A.; Stefaniak, Aleksandr B.; Jackson, Mark; Orandle, Marlene; Winn, Ava; Kashon, Michael; LeBouf, Ryan F.; et al.
Abstract: Background: Fused filament fabrication 3-D printing with acrylonitrile butadiene styrene (ABS) filament emits ultrafine particulates (UFPs) and volatile organic compounds (VOCs). However, the toxicological implications of the emissions generated during 3-D printing have not been fully elucidated. Aim and methods: The goal of this study was to investigate the in vivo toxicity of ABS-emissions from a commercial desktop 3-D printer. Male Sprague Dawley rats were exposed to a single concentration of ABS-emissions or air for 4 hours/day, 4 days/week for five exposure durations (1, 4, 8, 15, and 30 days). At 24 hours after the last exposure, rats were assessed for pulmonary injury, inflammation, and oxidative stress as well as systemic toxicity. Results and discussion: 3-D printing generated particulate with average particle mass concentration of 240 ± 90 µg/m³, with an average geometric mean particle mobility diameter of 85 nm (geometric standard deviation = 1.6). The number of macrophages increased significantly at day 15. In bronchoalveolar lavage, IFN-γ and IL-10 were significantly higher at days 1 and 4, with IL-10 levels reaching a peak at day 15 in ABS-exposed rats. Neither pulmonary oxidative stress responses nor histopathological changes of the lungs and nasal passages were found among the treatments. There was an increase in platelets and monocytes in the circulation at day 15. Several serum biomarkers of hepatic and kidney functions were significantly higher at day 1. Conclusions: At the current experimental conditions applied, it was concluded that the emissions from ABS filament caused minimal transient pulmonary and systemic toxicity.